2001
DOI: 10.1515/ling.2001.008
|View full text |Cite
|
Sign up to set email alerts
|

Analogy in morphology: modeling the choice of linking morphemes in Dutch

Abstract: This study argues that a productive but not fully regular morphological phenomenon, the choice of linking morphemes in Dutch nominal compounds, is based on analogy. In Dutch, a linking -s-or -en-can appear between the constituents of a nominal compound. We present production experiments that reveal strong evidence that the choice of linking morphemes in novel compounds is analogically determined by the distribution of linking morphemes in what we call the ''constituent families.'' A ''constituent family'' is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 25 publications
12
89
0
2
Order By: Relevance
“…In conclusion, previous studies (see, e.g., Ernestus & Baayen, 2003, 2004Krott, 2001;Krott et al, 2001;Skousen, 1989) have shown that the production of existing words and the creation of new morphologically complex forms in isolation are affected by the properties of semantic, phonological, morphological, and orthographical neighbors. Our results show that reading morphologically complex words in meaningful contexts is also affected by a word's lexical neighbors, and that these analogical effects are both intra-and interparadigmatic in nature.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In conclusion, previous studies (see, e.g., Ernestus & Baayen, 2003, 2004Krott, 2001;Krott et al, 2001;Skousen, 1989) have shown that the production of existing words and the creation of new morphologically complex forms in isolation are affected by the properties of semantic, phonological, morphological, and orthographical neighbors. Our results show that reading morphologically complex words in meaningful contexts is also affected by a word's lexical neighbors, and that these analogical effects are both intra-and interparadigmatic in nature.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies (e.g., Ernestus & Baayen, 2003, 2004Krott, 2001;Krott, Baayen, & Schreuder, 2001;Skousen, 1989) have shown that these stored words and word forms may affect each other's production as well as the formation of new morphologically complex forms. For instance, Krott and colleagues (Krott, 2001;Krott et al, 2001) showed that the probability and the speed with which a speaker of Dutch chooses a given interfix for a new compound highly correlates with the frequency of the interfix among the existing compounds with the same initial constituent as the new compound. If the initial constituent is followed by a certain interfix in many existing compounds, speakers often choose this interfix, and when they do so, they react fast.…”
mentioning
confidence: 97%
“…Krott, Baayen, and Schreuder (2001) made use of memory-based learning to predict interfixes in Dutch compounds, Plag, Kunter, and Lappe (2007) applied it to the analysis of stress patterns in English compounds, whereas Keuleers et al (2007) used it to study Dutch plural inflection. Keuleers (2008) provides a detailed comparison of memory-based learning with the rule-induction approach of Albright and Hayes (2003), focusing on regular and irregular verbs in English.…”
Section: Memory-based Learningmentioning
confidence: 99%
“…Schreuder , Bertram et al 2000, Krott et al 2001, which means that the relative frequency of base and derivative cannot be the only factor in play. Hence, frequency-based assessments of decomposability (and stacking) would need to incorporate morphological family effects as well as effects of relative frequency and absolute frequency.…”
Section: Problem 3: Predictions Concerning the Correlation Between Prmentioning
confidence: 99%